Do Communication and Critical Thinking Skills Influence Oral Presentation? Evidence from University Students - Vivi Indriyani; Herlin Triana; Hanifah Yulia Sari; Jasmienti Jasmienti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
The purpose of this research is to determine the relationship between communication skills and critical thinking skills on students' oral presentation skills. Using a quantitative approach, specifically causal associative research, this research investigates the relationship between the independent variables (communication and critical thinking) and the dependent variable (oral presentation). The research was conducted on Universitas Negeri Padang students taking Indonesian language courses in 2024, with a sample of 40 students selected through purposive sampling. Data collection involves performance tests (projects) and observation sheets, assessed using a predetermined rubric. Data were analyzed using multiple linear regression with the assistance of SPSS. The results revealed that communication skills and critical thinking skills jointly have a significant effect on students’ oral presentation abilities (F = 38.554, p < 0.05, R² = 0.676). However, when examined individually, only communication skills have a significant positive influence on students’ oral presentation performance (B = 0.637, p < 0.001), while critical thinking skills do not show a significant effect (B = 0.025, p = 0.881).